KEPEMIMPINAN KEPALA MADRASAH DALAM MENINGKATKAN MUTU PENDIDIKAN DI MADRASAH IBTIDAIYAH LITAHFIDZIL QUR’AN DARUSSALAM SENGKUBANG - Nasyarudin, Ahmad; Ubabuddin, Ubabuddin; Zabidi, Ahmad (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2024)
The leadership ability of the Head of Madrasah in directing the views of the community and teachers to work professionally so as to foster the level of public trust is increasing, it can be seen from the increasing number of students enrolling in Madrasah Litahfidzil Qur'an Mempawah. The approach of this research is descriptive qualitative with research subjects Madrasah Head, Deputy madrasah head, and Teachers. The data collection method uses observation, interview, and documentation methods. Data analysis technique uses three steps, namely data reduction, data presentation and conclusion drawing. The results of the study are: 1) the head of Madrasah has provided guidance to teachers with a maximum in the form of conducting regular meetings, providing encouragement by including teachers in training, workshorp, seminars, MGMP, 2) the head of Madrasah has provided guidance to students both in learning and extracurricular activities and fostering religious character by providing direction and motivation to students, 3) the head of Madrasah has been able to keep up with the development of science and technology well, and continues to improve its ability to keep up with the development of science and technology. 4) The implications of the leadership role of the madrasah head in improving the quality of education have been well seen from the professional improvement of teachers in carrying out their duties. For students, it has an impact on increasing learning achievement, achieving achievements in various competitions.